2017
DOI: 10.4314/tjpr.v16i3.27
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drug therapy problems among renal patients receiving care in some tertiary hospitals in Nigeria

Abstract: Purpose: To determine the prevalence of drug therapy problems (DTPs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 27 publications
5
23
2
Order By: Relevance
“…[ 37 , 43 ] Development of protocols and compiling and updating guidelines were also described in two studies [ 22 , 34 ]. Performing medication reconciliation [ 46 ]; providing patient medication counselling, education on disease status or medication, conducting motivational interviews to improve adherence were also reported [ 15 , 25 , 27 , 29 , 30 , 34 , 36 , 37 , 42 , 43 , 47 – 50 , 55 , 57 , 58 , 60 ]. A number of studies reported pharmacists’ participation in ward rounds [ 17 , 22 , 35 , 37 , 38 , 40 ], providing educational sessions to healthcare professionals [ 22 , 34 ] and performing activities such as medication use evaluations [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 37 , 43 ] Development of protocols and compiling and updating guidelines were also described in two studies [ 22 , 34 ]. Performing medication reconciliation [ 46 ]; providing patient medication counselling, education on disease status or medication, conducting motivational interviews to improve adherence were also reported [ 15 , 25 , 27 , 29 , 30 , 34 , 36 , 37 , 42 , 43 , 47 – 50 , 55 , 57 , 58 , 60 ]. A number of studies reported pharmacists’ participation in ward rounds [ 17 , 22 , 35 , 37 , 38 , 40 ], providing educational sessions to healthcare professionals [ 22 , 34 ] and performing activities such as medication use evaluations [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Across all studies, the pharmacists identified 5302 drug-related problems in 2933 patients. Pharmacists made 3160 recommendations to healthcare professionals with an acceptance rate varying from 33.3% in a community setting; [ 16 ] 46.43% in a dialysis unit; [ 59 ] to around 95% in hospital settings [ 17 , 24 , 42 , 51 , 52 , 57 ]. Only three studies reported the clinical significance of recommendations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation had been attributed to lack of motivation via rewards or reimbursement for the services as it is currently free-of-charge 18 . Pharmacists' lack of motivation might likely explain the growing trend of medication-related problems, particularly among outpatients with chronic diseases [19][20][21][22] . To date, no prior study has assessed the economic value of pharmacist-provided services in the hospital.…”
Section: Introductionmentioning
confidence: 99%